Celebrity Endorsement Analysis in Skintific Product Reviews on Tiktok on Generation Z Purchase Decisions (Case Study on Skintific Product Users in Bekasi) - Tami Nazua Putri; Djuni Thamrin; Matdio Siahaan (SEAN Institute, 2025)
This study aims to analyze the influence of celebrity endorsement in Skintific product reviews on the TikTok platform on purchasing decisions in Generation Z. The focus of this research is on users of Skintific products in the Bekasi area. The research method used is qualitative, with a case study approach. Data was collected through in-depth interviews with 15 informants who are Skintific users and actively follow product reviews on TikTok. The results of the study indicate that celebrity endorsement in Skintific product reviews on TikTok has a positive and significant influence on purchasing decisions in Generation Z. This study provides an in-depth understanding of how celebrity endorsement in product reviews on TikTok influence the perceptions, attitudes, and ultimately purchasing decisions of Generation Z towards Skintific product.